The Influence of Principal Leadership and Teacher Professionalism on Teacher Performance - Qur’ani, Nuzula; Ahyani, Nur; Eddy, Syaiful (Jurnal Pendidikan Tambusai, 2021)
This study aims to determine the effect of principal leadership and teacher professionalism on teacher performance. This type of research is a quantitative research design using ex post facto research design. The sample in this study was the total of all teachers in Public Senior High Schools in Sekayu District which consisted of 112 teachers. The data collection technique used a questionnaire. The data analysis technique used quantitative descriptive analysis techniques and multiple regression. The results of this study indicate that 1) there is a significant influence between principal leadership on teacher performance; 2) there is a significant influence between teacher professionalism on teacher performance 3) there is a significant effect of principal leadership and teacher professionalism together on teacher performance.